H2A.Z and H2B.Z double‐variant nucleosomes define intergenic regions and dynamically occupy var gene promoters in the malaria parasite Plasmodium falciparum - Petter, Michaela; Selvarajah, Shamista A.; Lee, Chin Chin; Chin, Wai Hoe; Gupta, Archna P.; Bozdech, Zbynek; Brown, Graham V.; Duffy, Michael F. (Molecular microbiology, 2013)
Summary Histone variants are important components of eukaryotic chromatin and can alter chromatin structure to confer specialized functions. H2B variant histones are rare in nature but have evolved independently in the phyla Apicomplexa and Trypanasomatida. Here, we investigate the apicomplexan‐specific Plasmodium falciparum histone variant Pf H2B.Z and show that within nucleosomes Pf H2B.Z dimerizes with the H2A variant Pf H2A.Z and that Pf H2B.Z and Pf H2A.Z occupancy correlates in the subset of genes examined. These double‐variant nucleosomes also carry common markers of euchromatin like H3K4me3 and histone acetylation. Pf H2B.Z levels are elevated in intergenic regions across the genome, except in the var multigene family, where Pf H2A.Z/Pf H2B.Z double‐variant nucleosomes are only enriched in the promoter of the single active var copy and this enrichment is developmentally regulated. Importantly, this pattern seems to be specific for var genes and does not apply to other heterochromatic gene families involved in red blood cell invasion which are also subject to clonal expression. Thus, Pf H2A.Z/Pf H2B.Z double‐variant nucleosomes appear to have a highly specific function in the regulation of P. falciparum virulence.